Analisis Pembiayaan Akad Mudharabah dan Musyarakah di Bank Syariah (Studi Kasus Bank BTN Syariah) - Muhammad Habibi Astono; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this study was to determine how the analysis process for the results of financing agreement in Islamic banks (Bank BTN Syariah case study). The results showed that of the theory 5C, Bank BTN Syariah using 4C theory (Character, Capacity, Capital, Collateral) or the so-called four pillars. As for the theory 6A (Analysis of Legal Aspects, Analysis Marketing Aspect, Aspect Analysis Technical Analysis Aspects of Management, Analysis of Financial Aspect, Aspect Analysis Socioeconomic) the Bank BTN Syariah overall use of the theory. Risk mitigation strategies of financing and loss at Bank BTN Syariah divided into two types namely risk strategy proactive and reactive risk strategy . Proactive risk strategy carried out by the analysis of the character , financial capability and guarantees borrowers. Reactive risk strategy carried out by the approach of friendship , rescheduling and restructuring measures, as well as the withdrawal of the guarantee.